Carrageenan-Induced Colonic Inflammation Is Reduced in Bcl10 Null Mice and Increased in IL-10-Deficient Mice. (23rd May 2013) - Bhattacharyya, Sumit; Xue, Liquan; Devkota, Suzanne; Chang, Eugene; Morris, Stephan; Tobacman, Joanne K.
Abstract : The common food additive carrageenan is a known activator of inflammation in mammalian tissues and stimulates both the canonical and noncanonical pathways of NF- κ B activation. Exposure to low concentrations of carrageenan (10 μ g/mL in the water supply) has produced glucose intolerance, insulin resistance, and impaired insulin signaling in C57BL/6 mice. B-cell leukemia/lymphoma 10 (Bcl10) is a mediator of inflammatory signals from Toll-like receptor (TLR) 4 in myeloid and epithelial cells. Since the TLR4 signaling pathway is activated in diabetes and by carrageenan, we addressed systemic and intestinal inflammatory responses following carrageenan exposure in Bcl10 wild type, heterozygous, and null mice. Fecal calprotectin and circulating keratinocyte chemokine (KC), nuclear RelA and RelB, phospho(Thr559)-NF- κ B-inducing kinase (NIK), and phospho(Ser36)-I κ B α in the colonic epithelial cells were significantly less (P < 0.001 ) in the carrageenan-treated Bcl10 null mice than in controls. IL-10-deficient mice exposed to carrageenan in a germ-free environment showed an increase in activation of the canonical pathway of NF- κ B (RelA) activation, but without increase in RelB or phospho-Bcl10, and exogenous IL-10 inhibited only the canonical pathway of NF- κ B activation in cultured colonic cells. These findings demonstrate a Bcl10 requirement for maximum development of carrageenan-induced inflammation and lack of complete suppression by IL-10 of carrageenan-induced inflammation.